Use of Lipid‐Lowering Drugs and the Risk of Cataract: A Population‐Based Nested Case‐Control Study. Issue 2 (21st August 2018) - Bezin, Julien; Mansiaux, Yohann; Noize, Pernelle; Salvo, Francesco; Bégaud, Bernard; Pariente, Antoine
Abstract : Eye lens membrane cells require high cholesterol concentrations that might be counteracted by lipid‐lowering drugs. Using a nationwide database, we conducted a nested case‐control study to evaluate the risk of cataract development associated with the use of lipid‐lowering drugs. Patients aged 45 years and over with first cataract surgery in 2014 (cases) and up to four controls matched on age, gender, diabetes, hypothyroidism, glucocorticoid use, cardiovascular risk, and area of residence were included in the study. Among the 2, 811 cases and 11, 106 matched controls included, analyses showed a significantly increased risk of cataract surgery for a cumulative exposure to fibrates exceeding 5 years (adjusted odds ratio (aOR) 1.58; 95% confidence interval (CI): 1.17–2.15), unlike cumulative exposure to statins, whatever the dose or duration of treatment (aORs from 1.00–1.08, none being significant). This study highlighted an increased risk of cataract surgery with prolonged use of fibrates but not of statins.